2002
DOI: 10.1093/jpepsy/27.3.245
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Internalizing and Externalizing Problem Behaviors on Recurrent Pain in Children

Abstract: Low self-control of emotions, indicated by internalizing and externalizing problem behaviors, was related to pain in both boys and girls; high self-control of emotions, indicated by constructive behavior, associated with pain only in girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 87 publications
(125 reference statements)
2
16
1
1
Order By: Relevance
“…In this longitudinal study [12], they demonstrated that there was no significant age effect on the association between adolescents’ functional somatic symptoms and externalizing problems. In the same line, Vaalamo et al [54] showed no differences in externalizing problem behaviours between 11–12 years old boys and girls with recurrent pain.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In this longitudinal study [12], they demonstrated that there was no significant age effect on the association between adolescents’ functional somatic symptoms and externalizing problems. In the same line, Vaalamo et al [54] showed no differences in externalizing problem behaviours between 11–12 years old boys and girls with recurrent pain.…”
Section: Discussionmentioning
confidence: 82%
“…aggression, negative affectivity) may attenuate individual’s coping capacity resulting in the intensification of the stress experience, that, in turn, exacerbates pain perception. Therefore, multiple, recurrent SHC may constitute behavioural manifestations that depict the low self-control capacity on managing intensification of emotions and activation of behaviour [54]. What is more, neurobiological findings regarding the close proximity of brain structures processing pain and negative emotion may provide impetus to study the association of emotional/behavioural functioning and SHC from a neuropsychological perspective as well [20].…”
Section: Discussionmentioning
confidence: 99%
“…The TR-MPNI items are presented in the form of statements (e.g., "Cannot concentrate on anything"), and the teachers are asked to rate pupils on every item on a four-point scale where 0=does not apply and 3=applies in a pronounced way. A factor analysis of the structure of the TR-MPNI (e.g., Pulkkinen et al 1999;Vaalamo et al 2002) has resulted in three main factors for externalizing problem behaviors, internalizing problem behaviors, and adaptive behaviors. The TR-MPNI scales have been validated against peer nominations and parental ratings in a large sample of Finnish twins (Pulkkinen et al 1999).…”
Section: Methodsmentioning
confidence: 99%
“…The TR-MPNI scales have been validated against peer nominations and parental ratings in a large sample of Finnish twins (Pulkkinen et al 1999). The scales differentiate between genders and are differentially affected by genetic and environmental factors (Vierikko et al 2006); are associated with heart rate reactivity , self-control (Kokkonen and Kinnunen 2006) and parenting and home atmosphere ; predict smoking initiation (Barman et al 2004) and recurrent pain (Vaalamo et al 2002); and are longitudinally predicted by self-esteem, hope, and academic achievements (Ciarrochi et al 2007). …”
Section: Methodsmentioning
confidence: 99%
“…Emotion dysregulation, considered a key component of complex traumatic stress (Ford, 2009), has been demonstrated to increase pain reporting in children (Connelly et al, 2012;Vaalamo, Pulkkinen, Kinnunen, Kaprio, & Rose, 2002). Using electronic diaries to collect repeated-measure, real-time data, Connelly et al (2012) demonstrated that participants reported less functional disability after successfully attenuating negative emotion.…”
Section: Pain Managementmentioning
confidence: 99%